Pendugaan Bobot Karkas, Persentase Karkas dan Tebal Lemak Punggung Babi Duroc Jantan Berdasarkan Umur Ternak - S.N. Aritonang; J. Pinem; S. Tarigan (Universitas Andalas, 2011)
The research for predicting of carcass weight, percentage of carcass and back fat thickness of male Duroc pig based on their age was done on one hundred and twenty male Duroc pigs. The pigs were divided into four different groups of their aged: A (240-270 days), B (271-300 days), C (301-330 days) and D (331-360 days). Survey method was done by using purposive quota sampling in Mabar Slaugther House, Medan. The variables observed were carcass weight, percentage of carcass, and back fat thickness of male Duroc pig. The prediction of variables which correlated with their aged were measured by using regression analysis. The result indicated that there was closely relation between animal age with carcass weight, percentage of carcass, and back fat thickness of male Duroc pig (P<0.01). The correlation coefficients were 0.989; 0.891 and 0.957 respectly.